Python : in easy steps - McGrath, Mike, 1956- (Leamington Spa, Warwickshire : In Easy Steps, 2013)
This title instructs you in how to program in Python, giving complete examples that illustrate each aspect with colourised source code.
Includes index.
Formerly CIP.
Keywords: Python (Computer program language)